Time consistency of fiscal and monetary policy a solution - Persson, Mats 1949-; Persson, Torsten 1954-; Svensson, Lars E. O. 1947- (National Bureau of Economic Research, 2005)
"This paper demonstrates how time consistency of the Ramsey policy - the optimal fiscal and monetary policy under commitment - can be achieved. Each government should leave its successor with a unique maturity structure for the nominal and indexed debt, such that the marginal benefit of a surprise inflation exactly balances the marginal cost. Unlike in earlier papers on the topic, the result holds for quite a general Ramsey policy, including timevarying polices with positive inflation and positive nominal interest rates. We compare our results with those in Persson, Persson, and Svensson (1987), Calvo and Obstfeld (1990), and Alvarez, Kehoe, and Neumeyer (2004)"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Fiscal policy -- Econometric models; Monetary policy -- Econometric models